KINERJA GURU BK DALAM MELAKSANAKAN PROGRAM BK LAYANAN BIMBINGAN KARIR DI SMA - Nadya Rahmadani (Jurnal Bimbingan dan Konseling Terapan, 2021)
Guidance and Counseling is a professional service conducted by the teacher of BK. One of the services in guidance and counseling to help learners to achieve growth, development, exploring and taking career decisions rationally and realistically based on information, self understanding and planning to achieve success in his life, with career guidance services. The purpose of this writing is to socialize the role of the BK teachers in implementing the BK program of career guidance services at the school and providing information about career guidance services activities that can be applied in schools. Career guidance services are conducted in order for learners to get the career information they needed so that students can create a mature career plan.